Clinical skills and nursing management in community health nursing – A qualitative study / Klinische Skills und Pflegemanagement im Rahmen von Community Health Nursing – Eine qualitative Studie - Lidauer Harald; Messina Chiara; Müller Gerhard; Wandl Bettina; Stummer Harald (International Journal of Health Professions)
Community Health Nursing plays a crucial role in primary care across Europe, with each country adopting distinct approaches. In Austria, the increasing healthcare demands necessitate a reevaluation of Community Health Nurses (CHNs) competencies, skills, and roles. The current descriptions of these aspects for CHNs in Austria lack comprehensiveness, posing a challenge to effectively meet these demands. Objective: The aim of the present study is to explore the clinical skills, health management, and nursing management competencies among CHNs.